The Current Student Services in Higher Education: Key Challenges and Solution Priorities - Moeurn Chantrea (Journal of Education Research, 2025)
The Ministry of Education, Youth, and Sports has launched higher education reforms to develop human capital since 2014. In 2024, the big reform was created in response to the vision of the Kingdom Vision 2050. Although higher education institutions have rapidly grown—from 8 in late 1997 to 194 by early 2025—student services remain underdeveloped and lack support. This qualitative study explores challenges in providing student services across Cambodian HEIs. Researchers used purposive sampling and interviewed 97 participants from seven stakeholder groups. Interviews included one-on-one and focus group discussions. Thematic analysis revealed challenges, such as assessment mechanisms, planning, infrastructure, facilities, budget constraints, student perspectives, and the commitment of university management. The findings further indicate that higher education institutions must take proactive and immediate measures to effectively support students’ learning trajectories. Drawing on stakeholder insights, this study recommends that Cambodian higher education institutions strengthen student services through comprehensive support frameworks. These measures will enhance student outcomes, institutional resilience, and the overall quality and competitiveness of higher education.